2012
DOI: 10.1007/s00586-012-2348-2
|View full text |Cite
|
Sign up to set email alerts
|

Establishing the diagnosis of tuberculous vertebral osteomyelitis

Abstract: Purpose The aim of this article has been to analyze the clinical and radiological data suggesting tuberculous vertebral osteomielitis (TVO), and then discuss the steps to be followed to achieve an aetiological diagnosis. Methods A thorough literature search was carried out to identify the best clinical and microbiological evidence for a fast and efficient diagnosis of TVO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
64
0
7

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(71 citation statements)
references
References 63 publications
0
64
0
7
Order By: Relevance
“…In fact current literature reviews do not even mention platelets count in TB spondylitis as a consideration [5,7,17]. The fact that TB of the spine has a delayed presentation compared to pulmonary TB makes the diagnosis even more challenging.…”
Section: Discussionmentioning
confidence: 99%
“…In fact current literature reviews do not even mention platelets count in TB spondylitis as a consideration [5,7,17]. The fact that TB of the spine has a delayed presentation compared to pulmonary TB makes the diagnosis even more challenging.…”
Section: Discussionmentioning
confidence: 99%
“…12 Hadjipavlou et al in 2003 examined osteometabolic disorders in 68 patients, in whom a total of 71 biopsy samples were obtained and in whom a microbial diagnosis was established in 30 (44%). 15 Colmenero and associates 7,8 evaluated specifically for tuberculous osteomyelitis; in 2004, 7 they compared open to percutaneous biopsies and found 61.7% and 48% of samples to be positive, respectively. 7 Yang and coworkers compared endoscopic and percutaneous techniques for biopsy and reported a positive result in 90% (18/20 patients) using endoscopic biopsy and in 47% (15/32 patients) using percutaneous biopsy.…”
mentioning
confidence: 99%
“…It is necessary for the differential diagnosis of brucellar, pyogenic and tuberculous spondylodiscitis. Colmenero et al [8] also reported that if there was no clear evidence of causative agent, the vertebral biopsy should be performed. In the presented case we have isolated the bacteria for diagnosis using biopsy.…”
Section: Dear Editormentioning
confidence: 99%